Chronic Poststernotomy Pain: Incidence, Risk Factors, Treatment, Prevention, and the Anesthesiologist's Role. Issue 6 (1st November 2017) - Kleiman, Amanda M.; Sanders, Daniel T.; Nemergut, Edward C.; Huffmyer, Julie L.
Abstract : Abstract: Chronic pain following median sternotomy is common after cardiac surgery. If left untreated, chronic sternal pain can reduce quality of life, affecting sleep, mood, activity level, and overall satisfaction. This has a significant societal effect given the large number of cardiac surgeries annually. Although a number of pathophysiologic processes and risk factors are assumed to contribute, the exact cause and major risk factors remain unknown. Moreover, the treatment of chronic poststernotomy pain is often inadequate, relying on opioids and other medications that provide minimal benefit to the patient and have significant adverse effects. Indeed, little is known regarding the prevention of chronic pain development following sternotomy. This review aims to present the current, limited data regarding the incidence, risk factors, treatment, and prevention of chronic poststernotomy pain and to identify areas of future research to improve management of this common complaint following cardiac surgery.